PENERAPAN GANTI RUGI DALAM PRAPERADILAN TINDAK PIDANA DIKAITKAN DENGAN KUHAP - TUBAGUS M Q C (Iustitia Omnibus (Jurnal Ilmu Hukum), 2020)
ABSTRACT Negligence or deliberately arresting and detaining someone can cause harm because it violates human rights, namely freedom of movement, dignity and dignity. The procedure for claiming compensation for wrongful arrest and detention must be regulated separately in a law. The research method used is a normative juridical approach and normative juridical research specifications. Meanwhile, the data analysis used qualitative juridical methods. The application of compensation in pretrial criminal offenses linked to the Criminal Procedure Code is that during the investigation stage, the police as the investigating party commits a deviant act, including torture, which aims to obtain a confession from the suspect. Constraints for law enforcement agencies in implementing compensation for pretrial criminal offenses are the lack of public knowledge, another obstacle is the difficulty of processing the right to compensation. Keywords: Compensation, pretrial, criminal action